2018
DOI: 10.7556/jaoa.2018.046
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Osteopathic Primary Care Residency Choice Decisions

Abstract: The highest percentage of participants indicated the third year of medical school was the time that they made residency selection decisions regarding what specialty they were interested in entering. No shifts regarding the importance of specific primary care residency choice factors were found between training status of respondents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This trend has been validated by another study which found that a majority of students entering medical school undecided in career choice elected to enter an NPC residency by their fourth year [24]. Moreover, a significant number of students see their third year of medical school as the time they decide on career specialty [25]. With no statistically significant difference between the costs incurred from preparing and sitting for board examinations of those who Strongly Agreed and Strongly Disagreed to the statement "I Plan to Enter a Primary Care Residency," our study further supports the theory that financial costs during undergraduate medical training are not a significant factor in career choice.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This trend has been validated by another study which found that a majority of students entering medical school undecided in career choice elected to enter an NPC residency by their fourth year [24]. Moreover, a significant number of students see their third year of medical school as the time they decide on career specialty [25]. With no statistically significant difference between the costs incurred from preparing and sitting for board examinations of those who Strongly Agreed and Strongly Disagreed to the statement "I Plan to Enter a Primary Care Residency," our study further supports the theory that financial costs during undergraduate medical training are not a significant factor in career choice.…”
Section: Discussionmentioning
confidence: 85%
“…Because of this smaller sample size, the influence of fourth-year students’ perceptions is underrepresented in our statistical models. Representation of these students' perceptions is important because it has been found that a majority of students who enter medical school, undecided on career choice, elect to apply for NPC residencies by their fourth year [25].…”
Section: Discussionmentioning
confidence: 99%
“…Quality scores ranged from 4 to 34 with a mean (SD) score of 18.6 (6.2) and a median score of 19 (Figure 2). Six articles found no benefit [17][18][19][20][21][22] or a negative impact 23 from the studied intervention; all others described interventions that appeared to have a positive influence on PC specialty choice.…”
Section: Resultsmentioning
confidence: 99%
“…In some national US studies that compared clerkship characteristics, the impact of a required primary care clerkship on specialty choice was found to be greater during the core clerkship year (commonly the third year) compared to the fourth year. 6,47 Other studies found no difference between clerkships in the third or fourth year. 24,56 One single-institution study of a required rural family medicine clerkship found that family medicine choice declined when the rotation was moved from the fourth year to the third year.…”
Section: Clerkship Quality Length and Timingmentioning
confidence: 96%